Gender Differences in Physical Education Motivation and Psychological Needs Satisfaction: Self-Determination Perspective - Harum Janata Kuncoro; Hijrah Maulidiah Afifah (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aimed to analyze gender differences in PE learning motivation and basic psychological needs satisfaction from the perspective of Self-Determination Theory (SDT) among students at SMK Muhammadiyah 1 Semarang. This study used a quantitative comparative research design involving 91 students consisting of 36 male and 55 female students. Data were collected using the Basic Psychological Needs in Physical Education (BPNS-PE) and Perceived Locus of Causality (PLOC) questionnaires. The data were analyzed using descriptive statistics, Kolmogorov–Smirnov normality tests, and the Mann–Whitney U test. The results showed that there was no significant difference in PE learning motivation between male and female students (p = 0.111). However, significant differences were found in basic psychological needs satisfaction (p = 0.001), where male students demonstrated higher levels of autonomy, competence, and relatedness compared to female students. These findings indicate that psychological experiences during PE learning activities may differ according to gender. Therefore, teachers need to create inclusive and supportive learning environments to improve students’ motivation and psychological needs satisfaction during PE learning.